1990
DOI: 10.1104/pp.94.3.1295
|View full text |Cite
|
Sign up to set email alerts
|

Similar Photosynthetic Performance in Low Light-Grown Isonuclear Triazine-Resistant and -Susceptible Brassica napus L

Abstract: Triazine-resistant plants grown under moderate to high photon flux density (PFD) conditions exhibit decreased photon yield, decreased light-saturated 02 evolution and slower growth than triazine-susceptible plants. In this study we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…our laboratory, however, revealed that resistant plants grown under low PFD do not exhibit the decreased photon yield seen in plants grown under moderate to high PFD conditions (15). A smaller difference in growth is also seen in resistant and susceptible plants grown under low PFD.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…our laboratory, however, revealed that resistant plants grown under low PFD do not exhibit the decreased photon yield seen in plants grown under moderate to high PFD conditions (15). A smaller difference in growth is also seen in resistant and susceptible plants grown under low PFD.…”
mentioning
confidence: 87%
“…The loss of vigor that accompanies the resistance trait, however, is a serious drawback. Studies with nearly isogenic resistant and susceptible lines of Brassica napus L. revealed that resistant plants grew more slowly (JJ Hart, unpublished data; 5) and had a lower photon yield (15,18) than susceptible plants. Development of productive resistant crop varieties will depend on our understanding of the molecular mechanism that brings about the loss of photosynthetic performance and growth in plants with the resistance trait.…”
Section: And Methodsmentioning
confidence: 99%
See 3 more Smart Citations